Nanosecond Triggering for Sealed-Off Cold Cathode Thyratrons With a Trigger Unit Based on an Auxiliary Glow Discharge - Korolev Yu. D. Yuriy Dmitrievich; Landl N. V. Nikolay Vladimirovich; Geyman V. G. Vladimir Garjevich; Bolotov A. V. Aleksandr Vladimirovich; Kasjyanov V. S. Vladimir; Nekhoroshev V. O. Vitaly Olegovich; Kovalsky S. S. Sergey Sergeevich (2015, 2015)
Title screen